Let Spirit Speak! : Cultural Journeys through the African Diaspora - Valdes, Vanessa Kimberly (Book collections on Project MUSE., 2012)
In this unique and groundbreaking collection, writers, critics, historians, and poets celebrate the cultural contributions of members of the African diaspora in the Western Hemisphere. Beginning with the cries and prayers of Gina Athena Ulysse to the Haitian loa Erzulie in the aftermath of the earthquake in Haiti, each writer in the collection engages in the recovering of the past, highlighting that which has been buried in the history of time. The contributors look at a wide range of artistic productions, from poetry and fiction, to art, music, and film, and martial arts produced in Cuba, Colombia, Brazil, Haiti, and the United States. Haitian Creole, Spanish, and English are brought together, giving the reader a vivid sense of the multiplicity of voices in the African diaspora. Rather than concentrate on the dispersion of peoples of African descent, this collection focuses instead on the multiple sites of origins in the Americas, as diasporic legacies are found throughout the continent.